Analysis of Organizational Culture, work environment and Stress Work On Employee Performance at the BPJS Office Meulaboh Branch Employment - Rawizah, Rawizah; Zakiyuddin, Zakiyuddin; Rismawati, Rismawati; Wintah, Wintah; Chandra Siahaan , Perry Boy (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2024)
At BPJS Employment Meulaboh, in the organizational culture between employees there are gaps in communication, and the work environment involves high workloads such as working hours that are longer than working hours which require employees to go home at 22.00 WIT which has an impact on stress levels and employee performance . This research aims to determine the impact of organizational culture, work environment and work stress on employees at the BPJS Employment Meulaboh Branch office. This type of research is qualitative research with a descriptive approach. The data in the research are 26 BPJS Employment employees. Using purposeful sampling technique, 4 key informants were obtained. Data collection uses direct interview techniques, documentation and participatory observation. The results of research on organizational culture variables have a positive impact on employee performance. The results of research on work environment variables have a positive impact on employee performance. The research results of the work stress variable have a negative impact on employee performance. So it can be concluded that organizational culture and environmental variables have a positive impact while work stress has a negative impact. Researchers hope that BPJS Employment will re-evaluate the role demands of employees in carrying out tasks that result in work stress.